Pengaruh Model Mind Mapping Terhadap Hasil Belajar Siswa Melalui Video Animasi Dalam Pembelajaran IPA Siswa Kelas V SD Negeri 2 Sungai Jeruju - Rika, Iyut; Sukardi, Sukardi; Rizhardi, Rury (Institut Teknologi Pendidikan Indonesia, 2022)
This study aims to determine the effect of the mind mapping model on student learning outcomes through animated videos for class V SD Negeri 2 Sungai Jeruju. Learning is essentially asking and answering questions. Asking questions is also important to increase students' interest in learning, increase students' curiosity, and can direct students' attention to a subject, as well as diagnose if there are difficulties that hinder student learning. Based on this, the problem in this study is whether it has an effect on the learning outcomes of fifthgrade science students at SD Negeri 2 Sungai Jeruju. The purpose of the study was to determine and describe student learning outcomes in class V SD Negeri 2 Sungai Jeruju. The research method used is quantitative methods with data collection techniques byobservation, interview documentation, and tests. The results of this study indicate that student learning outcomes are classified as high. In the classroom, students have started to ask a lot of questions and take advantage of the opportunity to ask questions during science learning.